La creatividad - Cotrina Angulo, Ana Melva (2019)
This lesson plan has been designed for the fourth grade B students of secondary at San Nicols high school of Trujillo city; having as title: The creativity; which was developed in the Personal Development, Citizenship and Civics curricular area._x000D_ The main objective was to develop skills, abilities and performances. For this, it was taken into account pedagogical processes such as motivation, problematization, prior knowledge, purpose, management, accompaniment, evaluation and metacognition Creativity is an innate ability in humans, which must be developed and it is necessary the secondary students level know its importance and know how they should know how to take advantage of it and use it in every moment of their lives._x000D_ Therefore, through the execution of this lesson plan, students had the opportunity to recognize their creative abilities, actively participating, working in teams, discussing the content, reflecting assertively, and finally they gave their topic conclusions.